CuO-In2O3Core-Shell Nanowire Based Chemical Gas Sensors. (9th February 2014) - Li, Xiaoxin; Li, Xiaogan; Chen, Ning; Li, Xinye; Zhang, Jianwei; Yu, Jun; Wang, Jing; Tang, Zhenan
Abstract : The CuO-In2 O3 core-shell nanowire was fabricated by a two-step method. The CuO nanowire core (NWs) was firstly grown by the conventional thermal oxidation of Cu meshes at 500°C for 5 hours. Then, the CuO nanowires were immersed into the suspension of amorphous indium hydroxide deposited from the In(AC)3 solution by ammonia. The CuO nanowires coated with In(OH)3 were subsequently heated at 600°C to form the crystalline CuO-In2 O3 core-shell structure, with In2 O3 nanocrystals uniformly anchored on the CuO nanowires. The gas sensing properties of the formed CuO-In2 O3 core-shell nanowires were investigated by various reducing gases such as hydrogen, carbon monoxide, and propane at elevated temperature. The sensors using the CuO-In2 O3 nanowires show improved sensing performance to hydrogen and propane but a suppressed response to carbon monoxide, which could be attributed to the enhanced catalytic properties of CuO with the coated porous In2 O3 shell and the p-n junction formed at the core-shell interface.